Neurobiology of Photophobia. Issue 1 (March 2019) - Burstein, Rami; Noseda, Rodrigo; Fulton, Anne B.
Abstract : Background: Photophobia is commonly associated with migraine, meningitis, concussion, and a variety of ocular diseases. Advances in our ability to trace multiple brain pathways through which light information is processed have paved the way to a better understanding of the neurobiology of photophobia and the complexity of the symptoms triggered by light. Purpose: The purpose of this review is to summarize recent anatomical and physiological studies on the neurobiology of photophobia with emphasis on migraine. Recent Findings: Observations made in blind and seeing migraine patients, and in a variety of animal models, have led to the discovery of a novel retino-thalamo-cortical pathway that carries photic signal from melanopsinergic and nonmelanopsinergic retinal ganglion cells (RGCs) to thalamic neurons. Activity of these neurons is driven by migraine and their axonal projections convey signals about headache and light to multiple cortical areas involved in the generation of common migraine symptoms. Novel projections of RGCs into previously unidentified hypothalamic neurons that regulate parasympathetic and sympathetic functions have also been discovered. Finally, recent work has led to a novel understanding of color preference in migraine-type photophobia and of the roles played by the retina, thalamus, and cortex. Summary: The findings provide a neural substrate for understanding the complexity of aversion to light in patients with migraine and neuro-ophthalmologic other disorders.